2018
DOI: 10.1530/joe-18-0090
|View full text |Cite
|
Sign up to set email alerts
|

Adipose and skeletal muscle thermogenesis: studies from large animals

Abstract: The balance between energy intake and energy expenditure establishes and preserves a 'set-point' body weight. The latter is comprised of three major components including metabolic rate, physical activity and thermogenesis. Thermogenesis is defined as the cellular dissipation of energy via heat production. This process has been extensively characterised in brown adipose tissue (BAT), wherein uncoupling protein 1 (UCP1) creates a proton leak across the inner mitochondrial membrane, diverting protons away from AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 180 publications
(212 reference statements)
1
59
0
2
Order By: Relevance
“…Consistent with the potentially lethal heat response in children with MHS, we found that the YS mice display a life-threatening response to heat that is also more severe in young mice and displays male predominance. Since adaptive thermogenesis, the finely regulated bioenergetic process that produces heat in response to changes in environmental temperature or diet [90][91][92] , plays a crucial role in the regulation of body temperature, we assessed the contribution of adaptive thermogenesis to the heat sensitivity of the YS mice. BAT and skeletal muscle are the principal sites for adaptive thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the potentially lethal heat response in children with MHS, we found that the YS mice display a life-threatening response to heat that is also more severe in young mice and displays male predominance. Since adaptive thermogenesis, the finely regulated bioenergetic process that produces heat in response to changes in environmental temperature or diet [90][91][92] , plays a crucial role in the regulation of body temperature, we assessed the contribution of adaptive thermogenesis to the heat sensitivity of the YS mice. BAT and skeletal muscle are the principal sites for adaptive thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…37 Skeletal muscle comprises 40%-50% of the mammalian body. 38 Due to its highly energetically active nature and abundance in the body, skeletal muscle accounts for 20%-25% of total BMR. 39 The main contributor to energy expenditure in skeletal muscle are the SERCA pumps, which account for nearly 50% of resting metabolic rate in skeletal muscle.…”
Section: Serca Uncoupling: a Role For Nnat?mentioning
confidence: 99%
“…Skeletal muscles can also be seen as a reservoir of amino acids, whose mobilization can serve for protein synthesis in various organs [1], and for liver glucose neosynthesis to ensure maintenance of glycemia during food deprivation [7]. In addition, a significant thermogenic role for skeletal muscle has been strongly suggested [8]. Finally, skeletal muscle exerts a number of endocrine or paracrine effects on various physiological processes through the production of the so-called myokines [9].…”
Section: Introductionmentioning
confidence: 99%